Effects of chronic carvedilol administration on blood pressure variability and target organ injury in rats with sinoaortic denervation - del Mauro, Julieta Sofía (2015)
Background: Increased blood pressure variability is a novel risk factor for the development of target organ injury both in hypertensive and normotensive subjects, so its reduction should be considered as a new therapeutic goal. Objective: The aim of this study was to evaluate the effect of long-term oral carvedilol treatment on blood pressure, blood pressure variability and target organ injury in the left ventricle and thoracic aorta in a model of blood pressure liability. Methods: Twelve male Wistar rats submitted to sinoaortic denervation were treated during 8 weeks with a single dose of carvedilol 30 mg/kg or vehicle. At the end of treatment, echocardiographic evaluation and blood pressure and short-term variability measurements were performed. Left ventricular and thoracic aortic weights were determined and histological samples were prepared from both tissues. Metalloproteinase MMP-2 and transforming growth factor β (TGF-β) were quantified in the left ventricle and thoracic aorta. Results: Carvedilol reduced systolic blood pressure and its variability in sinoaortic-denervated rats compared with the control group (126±5 vs. 142±11 mmHg, p<0.05; SD: 2.9±0.5 vs. 6.0±0.5 mmHg; p<0.05). A lower amount of connective tissue was found in carvedilol-treated animals. The expression of TGF-β decreased in both organs after carvedilol treatment. Conclusions: Chronic carvedilol treatment significantly reduces systolic blood pressure and its short-term variability in sinoaorticdenervated rats, decreasing the degree of left ventricular fibrosis.